Pelatihan Usaha Budidaya Maggot sebagai Bahan Pakan bagi Peternak Lele - Yudistria, Yuyus; Rusyandi, Deddy (Empowerment, 2023)
After the implementation of the new Sariwangi catfish farming business program in Parongpong District, West Bandung Regency in RW 12 Sariwangi Village, the majority of youth were very enthusiastic in the program implemented and the number of youth involvement in the program increased, marked by the increase in the number of cultivation groups. The increasing number of youth involved still has problems in developing catfish farming business, one of which is feed (not relying on 100% pellet feed), because if you only rely on pellets the difference in relative profits is very small, besides the price of pellets continues to increase while the selling price of catfish ups and down. Our solution to this problem is that maggot cultivation is needed as a feed ingredient for catfish farming farmers, namely by carrying out training on making maggot cultivation sites, management (planning, finance) with the implementation of the establishment program, which is expected to increase productivity and independence of catfish cultivation.  Setelah dilaksanakannya program usaha baru budidaya peternakan lele sariwangi yang terdapat di wilayah Kecamatan Parongpong Kabupaten Bandung Barat di RW 12 Desa Sariwangi mayoritas pemuda sangat antusias dalam program yang dilaksanakan dan semakin bertambah jumlah keterlibatan para pemuda dalam program tersebut, ditandai dengan bertambahnya jumlah kelompok budidaya. Bertambahnya jumlah pemuda yang terlibat masih memiliki masalah dalam pengembangan usaha budidaya peternakan lele salah satunya adalah pakan (tidak mengandalkan 100% pakan pelet), karena jika hanya mengandalkan pelet selisih keuntungan relative sangat sedikit, selain itu harga pelet yang terus mengalami kenaikan sedangkan harga jual lele naik turun. Solusi kami dengan adanya masalah tersebut maka diperlukan usaha budidaya maggot sebagai bahan pakan bagi peternak budidaya lele, yaitu dengan melaksanakan pelatihan pembuatan tempat budidaya maggot, pengelolaan (perencanaan, keuangan) dengan dilaksanakannya program pembentukan tersebut diharapkan dapat meningkatkan produktifitas dan kemandirian budidaya lele.